IMPACT OF CONCURRENT ELEVATION IN CO2 AND TEMPERATURE ON TUBER YIELD AND ASSOCIATED TRAITS OF POTATO GENOTYPES - Kumar, Prince (Potato Journal, 2022)
Carbon dioxide (CO2) concentration in the atmosphere is rising continuously and consequently global averagesurface temperature is anticipated to rise in near future which tends to affect tuber yield, associated physiological traits ofpotato. This necessitate to explore some resilient cultivars to counter the adverse impact of anticipated changing climatescenario. So, in order to explore such cultivars, an investigation was carried out in open top chambers having controlledfacility (CO2 and Temperature) at ICAR-CPRS, Jalandhar, Punjab. Two advance stage heat tolerant potato genotypes viz.,HT/7-1105 and HT/7-1329 and two commercial varieties, viz., Kufri Surya (heat tolerant) and Kufri Badshah were evaluatedunder three treatments, viz., (i) elevated CO2 (600 ppm) along with elevated temperature (30C rise over ambient); (ii)elevated CO2 (600 ppm) and (iii) ambient. Impact of higher temperature with elevated CO2 on tuber yield was negativeonly in Kufri Badshah (-10.17 t/ha). Response to CO2 enrichment, in terms of tuber yield, was positive in case of all thegenotypes i.e. Kufri Badshah, Kufri Surya, HT/7-1105 and HT/7-1329. These results suggest the overall superiority of KufriSurya and heat tolerant cultivars in terms of productivity under high CO2 and high temperature. Net photosynthesis (PS)rate was 34.4 Î¼mol CO2 m-2s-1 under elevated CO2 in Kufri Badshah that reduced to 27.10 Î¼mol CO2 m-2s-1 on exposure tohigh temperature (around 3oC) and CO2. These values were statistically significant over PS rate under ambient conditions.